Associations of NF-kappaB and Bax with Apoptosis in Varicose Veins of Women of Different Age Groups - Helle Evi Simovart; Andres Arend; Jüri Lieberg; Marina Aunapuu (International Journal of Vascular Medicine)
The study aimed at detecting apoptotic endothelial cells (ECs) and smooth muscle cells (SMCs) together with determining expression of NF-kappaB (p105/p50) and Bax in varicose vein walls. Women (n=35) undergoing the excision of varicose veins were divided into 3 groups: younger than 35 years (I), 36–50 years (II), and older than 50 years (III). Apoptosis was determined by the TUNEL method, NF-kappaB and Bax expression by immunohistochemistry. The percentage of apoptotic ECs and SMCs in the layers of varicose vein wall increased in groups II and III. NF-kappaB expression had the lowest level in Group II with particularly low level in the media. Contrariwise, Bax expression levels in Group II were increased. The study revealed that in varicose veins ECs and SMCs apoptosis increased with advancing age. If increase in apoptosis during earlier stages of varicosities is probably regulated by intrinsic pathway, then in older patients other signaling pathways may be involved.